2021
DOI: 10.1038/s41598-021-81429-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA-binding proteins that partner with Lin28a to regulate Dnmt3a expression

Abstract: Lin28 is an evolutionary conserved RNA-binding protein that plays important roles during embryonic development and tumorigenesis. It regulates gene expression through two different post-transcriptional mechanisms. The first one is based on the regulation of miRNA biogenesis, in particular that of the let-7 family, whose expression is suppressed by Lin28. Thus, loss of Lin28 leads to the upregulation of mRNAs that are targets of let-7 species. The second mechanism is based on the direct interaction of Lin28 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Highly expressed LIN28A can serve as a potential oncogenic factor that contributes to the tumorigenesis, development, and migration of ovarian, breast, liver, and colon cancers (27)(28)(29)(30)(31)(32)(33). Mechanism-wise, LIN28A can modulate the translation of its targeted mRNA and restrain let-7 expression in the posttranscriptional level, which both depend on the LIN28A protein's RNA-binding motif (34)(35)(36)(37)(38)(39)(40)(41)(42). For example, in a study on colorectal cancer, LIN28A was found to promote the development and progression of disease by regulating the expression of the mRNA GEFT (38).…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed LIN28A can serve as a potential oncogenic factor that contributes to the tumorigenesis, development, and migration of ovarian, breast, liver, and colon cancers (27)(28)(29)(30)(31)(32)(33). Mechanism-wise, LIN28A can modulate the translation of its targeted mRNA and restrain let-7 expression in the posttranscriptional level, which both depend on the LIN28A protein's RNA-binding motif (34)(35)(36)(37)(38)(39)(40)(41)(42). For example, in a study on colorectal cancer, LIN28A was found to promote the development and progression of disease by regulating the expression of the mRNA GEFT (38).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the reproducibility and sensitivity of our LIN28A interactome, we surveyed the currently known LIN28A interactors from 23 papers ( Amen et al., 2017 ; Balzer and Moss, 2007 ; Butland et al., 2014 ; Chang et al., 2013 ; Choudhury et al., 2014 ; Cox et al., 2010 ; Haenig et al., 2020 ; Hagan et al., 2009 ; Haq et al., 2019 ; Hein et al., 2015 ; Heo et al., 2009 ; Huttlin et al., 2021 ; Jin et al., 2011 ; Kawahara et al., 2011 ; Li et al., 2014 ; Luck et al., 2020 ; Maier et al., 2015 ; Mallanna et al., 2010 ; Marcon et al., 2014 ; Närvä et al., 2012 ; Parisi et al., 2021 ; Polesskaya et al., 2007 ; Wang et al., 2019 ), covering more than the BioGRID ( Chatr-Aryamontri et al., 2017 ) and IntAct ( Orchard et al., 2014 ) databases ( Table S1 ). Among 581 previously reported LIN28A interactors, 207 proteins were re-identified in our NPC data.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only one previous study used NPC-like cells (NE-4C) for surveying LIN28A-interacting proteins ( Yang et al., 2015b ) and found 40 interactors using GFP-fused Lin28a as the bait. Moreover, regardless of the cell types, most of the identified interactions with LIN28A were not assessed for RNA dependence or assessed but found to require RNA ( Heo et al., 2009 ; Närvä et al., 2012 ; Parisi et al., 2021 ; Polesskaya et al., 2007 ; Yang et al., 2015a ). Parsing the RNA-dependent/independent nature of interactions may provide another layer of information to help the mechanistic understanding of LIN28A.…”
Section: Introductionmentioning
confidence: 99%
“…An example is provided by the RNA-binding protein LIN28. In physiological conditions, LIN28 expression is highly restricted to ESCs (E14Tg2a cell line, Bay Genomics), where it is transiently induced after the exit of ESCs from the naïve ground state and downregulated in differentiated cells [42,181]. LIN28, together with OCT4, SOX2, and NANOG, can also reprogram somatic cells into induced pluripotent stem cells, functioning as important regulator of pluripotency [182,183].…”
Section: Pluripotency-regulating Mirnas In Escs and Cscs: The Role Of Lin28/let-7 Axismentioning
confidence: 99%